High-resolution Microbiome Analyses of Nine Psyllid Species of the Family Triozidae Identified Previously Unrecognized but Major Bacterial Populations, including Liberibacter and Wolbachia of Supergroup O - Inoue, Hiromitsu; Hirose, Yuu; Nakabachi, Atsushi (Microbes and Environments, 2022)
Psyllids (Hemiptera: Sternorrhyncha: Psylloidea) are plant sap-sucking insects that include important agricultural pests. To obtain insights into the ecological and evolutionary behaviors of microbes, including plant pathogens, in Psylloidea, high-resolution analyses of the microbiomes of nine psyllid species belonging to the family Triozidae were performed using high-throughput amplicon sequencing of the 16S rRNA gene. Analyses identified various bacterial populations, showing that all nine psyllids have at least one secondary symbiont, along with the primary symbiont “Candidatus Carsonella ruddii” (Gammaproteobacteria: Oceanospirillales: Halomonadaceae). The majority of the secondary symbionts were gammaproteobacteria, particularly those of the order Enterobacterales, which included Arsenophonus and Serratia symbiotica, a bacterium formerly recognized only as a secondary symbiont of aphids (Hemiptera: Sternorrhyncha: Aphidoidea). The non-Enterobacterales gammaproteobacteria identified in the present study were Diplorickettsia (Diplorickettsiales: Diplorickettsiaceae), a potential human pathogen, and Carnimonas (Oceanospirillales: Halomonadaceae), a lineage detected for the first time in Psylloidea. Regarding alphaproteobacteria, the potential plant pathogen “Ca. Liberibacter europaeus” (Rhizobiales: Rhizobiaceae) was detected for the first time in Epitrioza yasumatsui, which feeds on the Japanese silverberry Elaeagnus umbellata (Elaeagnaceae), an aggressive invasive plant in the United States and Europe. Besides the detection of Wolbachia (Rickettsiales: Anaplasmataceae) of supergroup B in three psyllid species, a lineage belonging to supergroup O was identified for the first time in Psylloidea. These results suggest the rampant transfer of bacterial symbionts among animals and plants, thereby providing deeper insights into the evolution of interkingdom interactions among multicellular organisms and bacteria, which will facilitate the control of pest psyllids.